2021
DOI: 10.1002/jbt.22888
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone has a neuroprotective effect against inflammation, oxidative stress, and endoplasmic reticulum stress in the brain cortex, medulla, and hippocampus due to doxorubicin

Abstract: Although doxorubicin (DOX) is used in many cancer treatments, it causes neurotoxicity. In this study, the effect of thymoquinone (THQ), a powerful antioxidant, on DOX-induced neurotoxicity was evaluated. In total, 40 rats were used and 5 groups were formed. Group I: control group (n = 8); Group II: olive oil group (n = 8); Group III: the THQ group (n = 8); THQ 10 mg/kg per day was given intraperitoneally (i.p.) throughout the experiment; group IV: DOX group (n = 8); On Day 7 of the experiment, a single dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…These suggest that CRTH2 deficiency attenuates doxorubicin-induced myocardial injury in mice. Doxorubicin may induce an increased expression of IL17A protein, which can be strongly suppressed by thymoquinone ( 51 ). We found a total of four drugs through molecular docking.…”
Section: Discussionmentioning
confidence: 99%
“…These suggest that CRTH2 deficiency attenuates doxorubicin-induced myocardial injury in mice. Doxorubicin may induce an increased expression of IL17A protein, which can be strongly suppressed by thymoquinone ( 51 ). We found a total of four drugs through molecular docking.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on TQ has demonstrated its pharmacological properties, including anti-inflammatory, anti-tumor, neuroprotective, and antioxidant effects (Ashraf et al 2011 ; Abdel-Daim et al 2020 ). TQ has been reported to have antioxidant effects by scavenging free radicals and enhancing the activity of internal antioxidant enzymes (Badary et al 2003 ), which has been associated with its neuroprotective activity (Saygin et al 2018 ; Abdel-Daim et al 2019 , 2020 ; Aboubakr et al 2021 ; Kaymak et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some neuropharmacological effects of TQ have been demonstrated. Among these neuropharmacological effects of TQ like anticonvulsant effects, muscle relaxants, and hypnotic effects, it is effects on motor coordination and locomotor activity were also investigated (6,7).…”
Section: Introductionmentioning
confidence: 99%